Anguilla rostrata - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
Anguilla rostrata (Lesueur, 1817) – American eel; Enguia-americana ② : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 17, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515